Evaluation of chronic gastritis in patients with Helicobacter pylori associated gastritis, gastroduodenitis and duodenal ulcer disease - , Nevin BAĞATUR, Yeşim ERALP, Aykut ÇELİK and , Ahmet DOBRUCALI and , Kadir BAL and , Murat TUNCER and , Suha GÖKSEL and , Hülya UZUNİSMAİL and , Ergun OKTAY (Turkish Journal of Gastroenterology 1, 2019)
-